The effect of melatonin and season on in vivo embryo production of Dohne Merino ewes - Buffoni, Andres; Vozzi, Pedro Alejandro; Gonzalez, Diego Martin; Rios, Glenda Laura; Viegas Bordeira, Jorge Horacio; Abecia, José Alfonso (2018)
To determine the effect of melatonin on embryo production in superovulated donor Dohne Merino ewes, two experiments were carried out at Trelew, Argentina (43° S 65° W), during the breeding and the anestrous seasons. Twenty-two ewes were used in experiment 1 (breeding season). Animals were divided into two groups: group M (melatonin, n = 11) received a melatonin implant 48 days before superovulatory treatment, and C (control, n = 11), non-treated. Two intrauterine artificial inseminations were performed 33 and 48 h after sponge removal. Embryos were collected 7 days after the onset of oestrus (58 days after the onset of melatonin treatments). Twelve ewes of the same breed were used in experiment 2, which was carried out during the anestrus season, under the same experimental procedures (group M, n = 6; group C, n = 6). Treated ewes presented a significant delay in the onset of oestrus during the breeding season (M: 31.10 ± 1.04; C: 25.20 ± 0.98 h; p < 0.05). Melatonin induced a significant reduction in the number of degenerated embryos per ewe during seasonal anestrus (M: 0.60 ± 1.74; C: 3.00 ± 1.74; p < 0.05). No differences between groups and seasons were observed for ovulation, fertilization and viability rates, and the number of viable embryos per ewe. In conclusion, our results indicate that the use of melatonin to improve embryo production in MOET sheep programs in the Dohne Merino breed at 43° S does not improve fertility and embryo viability. Although, a reduction of the number of degenerated embryos during the anestrous season was observed in the treated group.